Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1051/fruits:2002020
|View full text |Cite
|
Sign up to set email alerts
|

Caractères morphologiques deDetarium microcarpumGuill. et Perr. au sud du Mali

Abstract: Introduction. Detarium microcarpum is an important fruit-bearing species in the south of Mali. The objective of this work was the morphological characterization of certain populations of D. microcarpum, which would be a necessary step for a subsequent study of the genetic structure of the species. Materials and methods. Morphological observations related to twenty-three agronomic characters, studied on twenty-five trees selected from ten populations located in southern Mali. Results and discussion. The study s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 1 publication
1
15
0
7
Order By: Relevance
“…This is also to provide marketable products from farms that will generate income for resource-poor rural households. As such, it has led to an increasing interest in the domestication potential of some traditionally valued agroforestry trees in Africa, i.e., Detarium microcarpum Harms [2], Irvingia gabonensis (Aubry Lecomte ex O'Rorke) Baill. [3] and Sclerocarya birrea (A.Rich.)…”
Section: Introductionmentioning
confidence: 99%
“…This is also to provide marketable products from farms that will generate income for resource-poor rural households. As such, it has led to an increasing interest in the domestication potential of some traditionally valued agroforestry trees in Africa, i.e., Detarium microcarpum Harms [2], Irvingia gabonensis (Aubry Lecomte ex O'Rorke) Baill. [3] and Sclerocarya birrea (A.Rich.)…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, they help to fulfill households' subsistence and consumption needs in terms of energy and nutrition as well as medical and construction purposes. Secondly, they serve as a safety-net in times of crises (e.g., income shortages due to crop failure) and thirdly, some AFTPs provide regular cash income (Kouyaté 2005;Kalinganire et al 2007).…”
mentioning
confidence: 99%
“…A number of studies provided a description of the functions of some of the major species found in Sahelian parklands indicating that agroforestry tree products (AFTPs) can play three main functions in the household economy of rural communities living in or adjacent to the parkland (Kouyaté 2005;Kalinganire et al 2007). Firstly, they help to fulfill households' subsistence and consumption needs in terms of energy and nutrition as well as medical and construction purposes.…”
mentioning
confidence: 99%
“…and Perr. (Kouyaté and Van Damme, 2002), Ziziphus mauritiana Lam. (Koné et al, 2009), Allanblackia floribunda Oliver (Atangana, 2010), Adansonia digitata L. (Assogbadjo et al, 2006(Assogbadjo et al, , 2008(Assogbadjo et al, , 2009Kyndt et al, 2009 ;Kouyaté et al, 2011), Milicia excelsa (Welw.)…”
Section: Variation Morphologique Et Production Fruitière De La Populamentioning
confidence: 99%